Contact tracing in the hospital setting for COVID-19: An experience from AIIMS, New Delhi - Devashish Desai; Anivita Aggarwal; Komal Singh; Shivdas Rajaram Naik; Arvind Kumar; Ravneet Kaur; Naveet Wig (Wolters Kluwer Medknow Publications, 2022)
In this commentary, we relate our experience with contact tracing within the setting of a tertiary care institute and how it evolved over the course of the pandemic. The need for a contact tracing mechanism arose when the hospital's first COVID-19 positive employee emerged at the end of March 2020. The central contact tracing team (CCTT) was subsequently established to perform this essential function. We describe the methodology followed by the CCTT as well as the practical hurdles encountered during contact tracing. The benefits of setting up an institutional contact tracing mechanism cannot be overemphasized. We strongly recommend setting up such a mechanism in all health-care institutes, not just for the COVID-19 pandemic but also for future respiratory disease outbreaks as well.